2023
DOI: 10.1136/bmjopen-2023-072999
|View full text |Cite
|
Sign up to set email alerts
|

Two-step offer and return of multiple types of additional genomic findings to families after ultrarapid trio genomic testing in the acute care setting: a study protocol

Abstract: IntroductionAs routine genomic testing expands, so too does the opportunity to look for additional health information unrelated to the original reason for testing, termed additional findings (AF). Analysis for many different types of AF may be available, particularly to families undergoing trio genomic testing. The optimal model for service delivery remains to be determined, especially when the original test occurs in the acute care setting.Methods and analysisFamilies enrolled in a national study providing ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Our study identified a high expected uptake rate of AF (93%). While there may be multiple factors influencing AF uptake rates 12 , emerging evidence suggests that rates may range between 80% and 98% 13 15 . A Canadian study by Regier et al 16 , elicited societal preferences for the return of AF from genomic sequencing using a discrete-choice experiment method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study identified a high expected uptake rate of AF (93%). While there may be multiple factors influencing AF uptake rates 12 , emerging evidence suggests that rates may range between 80% and 98% 13 15 . A Canadian study by Regier et al 16 , elicited societal preferences for the return of AF from genomic sequencing using a discrete-choice experiment method.…”
Section: Discussionmentioning
confidence: 99%
“…Our work benefited from a national recruitment of families with children affected by rare conditions through the Australian Genomics and Melbourne Genomics programs. The two-step offer for AF analysis model has been argued to offer the advantage of a temporal separation of the AF offer from the offer of diagnostic testing, which reduces families’ decision burden during a period of high distress, while providing the opportunity to receive more information and reflect on the risks and benefits of the analysis for AF 12 , 19 . Building on this principle, we provided in-depth information about AF through the adapted version of Genetics Adviser 20 , to further enhance the formation of preferences and support informed choice responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This kind of staged approach has been used in other settings where GS is being used in time-critical settings to obtain a diagnosis and secondary information is offered a few months after the initial testing. 37 …”
Section: Discussionmentioning
confidence: 99%